Prenatal Diagnosis of Treacher-Collins Syndrome Using Three-Dimensional Ultrasonography and Differential Diagnosis with Other Acrofacial Dysostosis Syndromes - Daniela Cardoso Pereira; Luiz Claudio Silva Bussamra; Edward Araujo Júnior; Carolina Leite Drummond; Luciano Marcondes Machado Nardozza; Antonio Fernandes Moron; José Mendes Aldrighi (Case Reports in Obstetrics and Gynecology)
Treacher-Collins syndrome (TCS) is a rare dominant autosomal anomaly resulting from malformation or disruption of the development of the first and second branchial arches. It is characterized by micrognathia, malar hypoplasia, and malformations of the eyes and ears. The prenatal diagnosis using two-dimensional ultrasonography (2DUS) is characterized by identification of facial malformations together with polyhydramnios. Three-dimensional ultrasonography (3DUS) has the capacity to spatially display these facial malformations, thus making it easy for the parents to understand them. We present a case of TCS diagnosed in the 33rd week using 3DUS, with postnatal confirmation using cranial computed tomography and anatomopathological analysis.